Tree species is the major factor explaining C:N ratios in European forest soils - Cools, N.; Vesterdal, L.; De Vos, B.; Vanguelova, E.; Hansen, K.; Vos, B. De (Forest Ecology and Management, 2013)
The C:N ratio is considered as an indicator of nitrate leaching in response to high atmospheric nitrogen (N) deposition. However, the C:N ratio is influenced by a multitude of other site-related factors. This study aimed to unravel the factors determining C:N ratios of forest floor, mineral soil and peat top soils in more than 4000 plots of the ICP Forests large-scale monitoring network. The first objective was to quantify forest floor, mineral and peat soil C:N ratios across European forests. Secondly we determined the main factors explaining this C:N ratio using a boosted regression tree analysis (BRT), including fifteen site and environmental variables. Ninety-five percent of the C:N ratios were between 16 and 44 in the forest floor, between 13 and 44 in the peat topsoil and between 10 and 32 in the mineral topsoil. Within the aerated forest floor and the mineral soil, the C:N ratios decreased with depth, while in the hydromorphic forest floor and the peats no clear trend with depth was observed. Tree species was clearly the most important explanatory variable for the C:N ratio in both forest floors and topsoils, while it was soil type in the deeper mineral soil layers. The lowest C:N ratios both in the forest floor and the top mineral soil were found in black locust (Robinia pseudoacacia L.) and black alder (Alnus glutinosa L.) stands, both N fixing tree species. While in the forest floor the highest C:N ratios were found in evergreen species like pine, cork oak (Quercus suber L.) and eucalyptus, the pine species and Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) showed the highest C:N ratios in the mineral soil. The second most important explanatory variable in the forest floor and mineral topsoil was the biogeographical zoning (ecoregion). In the peat topsoil and in the deeper mineral soil layers it was the humus type. Deposition and climatic variables were of minor importance at the European scale. Further analysis for eight main forest tree species individually, showed that the influence of environmental variables on C:N ratios was tree species dependent. For Aleppo pine (Pinus halepensis Miller) and holm oak (Quercus ilex L.), both with a typical Mediterranean distribution, the relationship between N and S deposition and C:N ratio appeared to be positive. This study suggests that applying C:N ratios as a general indicator of the N status in forests at the European level, without explicitly accounting for tree species, is too simplistic and may result in misleading conclusions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon; Forest floor; ICP forests; Mineral soil; nitrogen; Tree species

Modelling leaf mass per area in forest canopy as affected by prevailing radiation conditions - Davi, H.; Barbaroux, C.; Dufrêne, E.; François, C.; Montpied, P.; Bréda, N.; Badeck, F. (Ecological Modelling, 2008)
Leaf mass per area (LMA) is a key leaf trait, which conditions the assessment of carbon balance and the adaptation of the species to their environment. LMA decreases exponentially within the canopy at a lower rate coefﬁcient (kLMA) than the extinction coefﬁcient (kPAR) of photosynthetically active radiation (PAR); consequently the canopy is not fully optimized for the carbon balance. A new algorithm to simulate LMA in forest canopies is developed. The algorithm is based on a relationship between LMA of leaves at a given canopy depth and PAR, that they absorb, during leaf growth. The LMA sub-model is then tested against independent experimental data to demonstrate its validity to assess (i) the LMA vertical distribution inside the canopy, (ii) its evolution during the season and (iii) the variability observed between sites, years and species. Then, the LMA sub-model is coupled with a process-based model simulating carbon, water and energy balances in forest ecosystem. The coupled model is applied to a sensitive analysis for a case study in a beech forest.
Keywords: Carbon; Fagus sylvatica L.; Leaf mass per area; Modelling; Photosynthetically active radiation; Quercus ilex L.; Quercus petraea (Matt.) Liebl.